Choosing an effective insulation for reservoirs with high-temperature pitch - Назаренко, Ирина Анатольевна (Technology audit and production reserves, 2013)
The article analyzes heat-insulating materials to reduce heat losses to the environment of reservoirs with a high-temperature pitch. At enterprises producing graphitized electrodes there are strict requirements for storage technology of high-temperature pitch, so thermal insulation in addition to power-saving features, enables the processes of heating of the pitch at a given temperature level. The article justifies the thermal insulation for vertical steel reservoirs. There is a comparison of the thermal insulation Nobasil LSP and TEMP-COAT. It was shown that reduction of heat losses would reduce a coolant flow by 30%. From the point of view of the economic reasonability the thermal insulation TEMP-COAT is recommended, because the payback period is 1.7 times smaller. These results can be used as bases for the design of energy-efficient modes of operation of pitch enterprise "Ukrgrafit."